Purificação e caracterização de uma CA2+ -ATPase de larva de Pachymerus nucleorum (Fabricius) (Coleoptera: Chrysomelidae: Bruchinae) - Melo, Hugo Christiano Soares (2008)
CHAPTER III: Myosin can be precipitated by freezing and thawing the soluble fraction of different mammal tissues. In this work, the objective was to precipitate ATPase similar to myosin starting from the soluble fraction of P. nucleorum larva. The soluble fraction was frozen at -20 oC and thawed after 48 h and centrifuged at 45.000 g x 40 min. The precipitaded was recovered and successively washed with buffer solution at pH 7.5 and 9.0. Later, ATPase was solubilized through the treatment of the precipitate with buffer solution pH 9.0 containing 0.5 mmol.L-1 NaCl. The main peptides of the ATPase fraction presented Mr of 205 and 45 kDa. That fraction expressed high Ca2+-ATPase activity, but it did not present or K+/EDTA-ATPase activity. However, Mg2+-ATPase activity appears in the presence of F-actin, and identification by PMF shows similarity of p205 with myosin heavy chain of Tribolium castaneum. The Ca2+-ATPase activity was not inhibited by 140 μmol.L-1 thapsigargin, 1.7 mmol.L-1 ouabain or 1 mmol.L-1 azide, but was greatly inhibited by magnesium. The enzyme did not hydrolyze AMP or PPi and only slightly hydrolyze ADP and GTP. In this work, we isolated a polypeptide from 205 kDa of P. nucleorum larvae that was co-purified with Ca2+-ATPase activity.